Acute and Chronic Testosterone Response to Blood Flow Restricted Exercise - Loenneke, J. P.; Wilson, J. M.; Pujol, T. J.; Bemben, M. G. (Hormone and Metabolic Research, 2011)
The American College of Sports Medicine recommends lifting a weight of at least 70% 1RM to achieve muscular hypertrophy as it is believed that anything below this intensity rarely produces substantial muscle growth. At least part of this recommendation is related to elevated systemic hormones following heavy resistance training being associated with skeletal muscle hypertrophy. Despite benefits of high intensity resistance training, many individuals are unable to withstand the high mechanical stresses placed upon the joints during heavy resistance training. Blood flow restricted exercise offers a novel mode of exercise allowing skeletal muscle hypertrophy at low intensities, however the testosterone response to this exercise has yet to be discussed. The acute and chronic testosterone response to blood flow restricted exercise appears to be minimal when examining the current literature. Despite this lack of response, notable increases in both size and strength are observed with this type of exercise, which seems to support that systemic increases of endogenous testosterone are not necessary for muscular hypertrophy to occur. However, definitive conclusions cannot be made without a more thorough analysis of responses of androgen receptor density following blood flow restricted exercise. It may also be that there are differing mechanisms underlying hypertrophy induced by high intensity resistance training and via blood flow restricted exercise.
Keywords: KAATSU; vascular occlusion; anabolic hormone; hypertrophy